A Kinetic Approach to Saponin Extraction During Washing of Quinoa (Chenopodium Quinoa Willd.) Seeds - Lemus-Mondaca, R (2013)
The aim of this work was to show that the leaching process of saponins from quinoa (Chenopodium quinoa Willd.) seeds during washing with water, as is generally practiced by people in South America, can be modeled using mathematical expressions related to Fick s second law. Experimental data were obtained through batch extraction with a ratio of quinoa to water of 1:10 under constant agitation for processing time between 15 and 120 min at 20, 30, 40, 50 and 60C. It was found that residual saponin concentration in the quinoa seeds decreased as washing temperature increased. Leaching rate followed the Arrhenius relationship, with calculated effective saponin diffusion coefficient between (5.05 ± 0.15) × 10-10 and (32.50 ± 1.65) × 10-10m2/s as the temperature increased from 20 to 60C. Several mathematical models to describe the kinetic behavior of the leaching process were analyzed. The modified Henderson-Pabis model had the best fit quality as shown by statistical analysis. PRACTICAL APPLICATIONS During processing of quinoa for human consumption, a washing process is necessary to remove most of the bitter saponins found in the seeds, as this type of saponin is considered to be a serious antinutritional factor. For industrial scale-up of this processing step, leaching behavior of the saponin is of crucial importance to find the best design parameters and the most cost-effective process conditions. This helps reduce energy waste and optimize water flow rate in a continuous washing process. The present study used well-known models to explain saponins leaching kinetics from the quinoa seeds with water at different temperatures. The best mathematical model with its justification was also determined, which is generally the most economical way to proceed. © 2012 Wiley Periodicals, Inc.